Limitations of the Parsonnet score for measuring risk stratified mortality in the north west of England. Issue 1 (1st July 2000) - Wynne-Jones, K; Jackson, M; Grotte, G; Bridgewater, B
Abstract : OBJECTIVE: To study the use of the Parsonnet score to predict mortality following adult cardiac surgery. DESIGN: Prospective study. SETTING: All centres performing adult cardiac surgery in the north west of England. SUBJECTS: 8210 patients undergoing surgery between April 1997 and March 1999. MAIN OUTCOME MEASURES: Risk factors and in-hospital mortality were recorded according to agreed definitions. Ten per cent of cases from each centre were selected at random for validation. A Parsonnet score was derived for each patient and its predictive ability was studied. RESULTS: Data collection was complete. The operative mortality was 3.5% (95% confidence interval 3.1% to 3.9%), ranging from 2.7% to 3.8% across the centres. On validation, the incidence of discrepancies ranged from 0% to 13% for the different risk factors. The predictive ability of the Parsonnet score measured by area under the receiver operating characteristic curve was 0.74. The mean Parsonnet score for the region was 7.0, giving an observed to expected mortality ratio of 0.51 (range 0.4 to 0.64 across the centres). A new predictive model was derived from the data by multivariate analysis which includes nine objective risk factors, all with a significant association with mortality, which highlights some of the deficits of the Parsonnet score. CONCLUSIONS: Risk stratified mortality data were collected on 100% of patients undergoing adult cardiac surgery in two years within a defined geographical region and were used to set an audit standard. Problems with the Parsonnet score of subjectivity, inclusion of many items not associated with mortality, and the overprediction of mortality have been highlighted.